2014
DOI: 10.1002/rcr2.80
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional intramuscular administration of tPA / DN ase for pleural infection

Abstract: Intrapleural tissue plasminogen activator (tPA) and deoxyribonuclease (DNase) therapy has recently been shown to improve outcomes in pleural infection in a randomized trial. Published literature, to date, consists of only ∼50 patients who had received tPA/DNase. Safety data of this regimen remain limited. Pleural contents often track along chest drains, but the effect of tPA/DNase on subcutaneous tissues is unknown. We report a patient treated in another center who was unintentionally administered up to six in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Popowicz et al 8 described two courses of intrapleural tPA with DNase administered for two different loculated pleural effusions with good clinical outcome and no adverse effects. The same author illustrated a patient who was unintentionally administered up to six instillations of tPA (10 mg) and DNase (5 mg) intramuscularly via a malpositioned chest drain 9. The patient was reported to have experienced minimal discomfort but no signs of tissue inflammation or necrosis on CT thorax.…”
Section: Discussionmentioning
confidence: 99%
“…Popowicz et al 8 described two courses of intrapleural tPA with DNase administered for two different loculated pleural effusions with good clinical outcome and no adverse effects. The same author illustrated a patient who was unintentionally administered up to six instillations of tPA (10 mg) and DNase (5 mg) intramuscularly via a malpositioned chest drain 9. The patient was reported to have experienced minimal discomfort but no signs of tissue inflammation or necrosis on CT thorax.…”
Section: Discussionmentioning
confidence: 99%
“…A case report describes a patient exposed to six doses of 10 mg of tPA mixed with 5 mg of DNase in 20 ml of normal saline administered intramuscularly via a malpositioned chest tube. The patient experienced mild discomfort and imaging revealed mild swelling though no hemorrhage and tissue necrosis . The second potentially harmful case would have resulted in tPA being instilled into a line that was internally broken, resulting in systemic dosing of tPA.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent clinical trials have demonstrated the efficacy of IPFT in adult patients with empyema ( Thommi et al, 2007 ; Rahman et al, 2011 ; Thommi et al, 2012 ; Popowicz et al, 2014a ; Popowicz et al, 2014b ; Nie et al, 2014 ; Piccolo et al, 2014 ; Piccolo et al, 2015 ; Barthwal et al, 2016 ; Majid et al, 2016 ; Mehta et al, 2016 ; Vial et al, 2016 ; Bishwakarma et al, 2017 ; Popowicz et al, 2017 ; Beckert et al, 2019 ; Godfrey et al, 2019 ). However, the strikingly higher mortality in adults does not allow for extrapolation of treatment strategies used in pediatrics and speaks to the imperative for preclinical studies focused on the mechanisms governing development and resolution of empyema in adults.…”
Section: Treatment Of Advanced Stage Empyema In Adults Cannot Be Extrapolated From Pediatric Researchmentioning
confidence: 99%
“…Over the past decade, cost effective ( Asciak et al, 2019 ) IPFT with a combination of tPA and deoxyribonuclease (DNase) (Dornase), as demonstrated in the Multicenter Intrapleural Sepsis Trial 2 (MIST2) ( Rahman et al, 2011 ), has been broadly embraced as IPFT for empyema ( Abu-Daff et al, 2013 ; Popowicz et al, 2014a ; Popowicz et al, 2014b ; Israel and Blackmer, 2014 ; Piccolo et al, 2014 ; Piccolo et al, 2015 ; Majid et al, 2016 ; Bishwakarma et al, 2017 ; Majid et al, 2017 ; Popowicz et al, 2017 ; Innabi et al, 2018 ; Kheir et al, 2018 ; Fitzgerald et al, 2019 ; Fitzgerald et al, 2021 ). A recent expert consensus statement ( Chaddha et al, 2021 ) described the level of severity of empyema that should be treated with tPA/DNase injected concurrently, appropriate dosing (10/5 mg, respectively), dwelling time, dose schedule (twice a day), and an algorithm for IPFT, thus re-establishing a universal “one for all” treatment approach to empyema based on the MIST2 protocol.…”
Section: The Mist2 Protocol: Attempts At Revision Reflect the Failure Of A “One Dose For All” Conceptmentioning
confidence: 99%